Utilisation of Guava discarded product: extraction of antioxidant from guava leaves using an Ultrasound Assisted Method - Mariani Rajin (2017)
Background: In this research, guava leaves are utilised as a potential source of natural antioxidants. Various extraction techniques have been applied for the extraction of phenolic compounds from plants. However, the high temperature and long extraction time used in these methods can cause degradation of the bioactive compounds. In order to overcome this limitation, ultrasound assisted extraction is one of the techniques that can be applied. The advantages of this method include increased extraction yield, less solvent amount required, lower temperature and shorter extraction time.